2007
DOI: 10.1096/fj.06-7861com
|View full text |Cite
|
Sign up to set email alerts
|

Lung‐specific nuclear reprogramming is accompanied by heterokaryon formation and Y chromosome loss following bone marrow transplantation and secondary inflammation

Abstract: Cell fusion is one mechanism by which bone marrow-derived cells (BMDCs) take on the gene expression pattern of nonhematopoietic cells. This process occurs in a number of organs with postengraftment injury but has never been found in the lung. We performed bone marrow (BM) transplant in a murine model of lung inflammation to test whether transplanted BMDCs develop lung-specific gene expression by fusing with diseased pneumocytes. Mice lacking the lung-specific protein surfactant protein C (Sp-C) were lethally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…
AbstractTransplanted bone marrow derived cells (BMDCs) have been reported to fuse with cells of diverse tissues [1][2][3][4][5][6][7][8][9][10][11][12][13] , but the extremely low frequency of fusion has led to the view that such events are biologically insignificant. Nonetheless, in mice with a lethal recessive liver disease (tyrosinaemia), transplantation of wild type BMDCs restored liver function by cell fusion and rescued the mice from death 3, 9 , indicating that cell fusion can have beneficial effects.
…”
mentioning
confidence: 99%
“…
AbstractTransplanted bone marrow derived cells (BMDCs) have been reported to fuse with cells of diverse tissues [1][2][3][4][5][6][7][8][9][10][11][12][13] , but the extremely low frequency of fusion has led to the view that such events are biologically insignificant. Nonetheless, in mice with a lethal recessive liver disease (tyrosinaemia), transplantation of wild type BMDCs restored liver function by cell fusion and rescued the mice from death 3, 9 , indicating that cell fusion can have beneficial effects.
…”
mentioning
confidence: 99%
“…Still another possibility is fusion with resident cells that then affects cell and vascular function. Transdifferentiation and true plasticity of hematopoietic cells has been called into question due to earlier, less rigorous studies to detect fusion events (14,17,22,23). Cell fusion by definition results in a heterokaryon with combined donor cell and recipient DNA.…”
mentioning
confidence: 99%
“…There are elegant published data demonstrating that fusion of a macrophage, which would be BM derived, with an injured hepatocyte in vivo can lead to reprogramming of the macrophage nucleus so that it expresses what are considered to be liverspecific genes (31,32). We have demonstrated that 20 to 50% of BMDE in the lung after BM transplantation are due to fusion (33). Thus, cell fusion has been proven to be at least one mechanism by which BMDE develop.…”
Section: Potential Mechanisms By Which Bm Cells Take On the Gene Exprmentioning
confidence: 84%
“…These authors are to be commended for this reconsideration, as much of the data so far published on BMDE is dependent on morphology alone, and the staining and resolution of the imaging techniques are not always optimized for definitive identification of BMDE in lung tissue. More definitive identification approaches have involved the use of confocal microscopy and also the identification of single individual BM-derived epithelial cells analyzed after digestion and isolation of purified cells from the tissues (33), which allows one to avoid the risk of misinterpretation of the data due to one cell overlapping another.…”
Section: Brief Overview Of Published Literature On Bm-derived Lung Epmentioning
confidence: 99%